Enhancing University Admission Test Readiness Through an Android-Based CBT Platform in a Semi-Rural Islamic School - Indana Lazulfa; Reza Augusta Jannatul Firdaus; Ahmad Heru Mujianto; Muhammad Husein Hanafiyah; Lilis Karimatun Nisa' (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2026)
The activities aim to improve students’ readiness for the admission test through Android-based coaching integrated into simulation-based learning. Activity implementation focuses on developing simulation-based learning modules aligned with university admission tests, integrating m-learning with a computer-based test with automated grading, and coaching students in the use of the applications for self-study. The participants comprised 16 students and six teachers. The activity results showed a significant increase in student readiness: 11 of 16 students (68.75%) increased their post-training scores, with an average gain of 20.73% relative to pre-test scores. In addition to improving academic achievement, students showed a decrease in anxiety about computer-based exams and an increase in confidence and learning independence. On the other hand, teachers gain greater competence in managing digital evaluations and using learning outcome analytics to improve learning. The main contribution of this activity is the availability of an Android-based CBT ecosystem that is contextual, sustainable, and aligned with the limitations of semi-rural school infrastructure, as well as the strengthening of teachers' and students' capacity to navigate the digital transformation of education. This program demonstrates that the use of students' existing mobile devices can be an effective means of reducing the digital divide and increasing SNBT readiness in the Madrasah environment.